Integratory project rehabilitation of abandoned buses for the creation of a theater - Calero Villarreal, Richard Manolo; Jiménez. Fernández, Jorge Armando; Herrera Castillo, Jeremy Isaías; Segovia Chiliquinga, Gerardo Javier (Ingeniería Química y Desarrollo, 2024)
The present investigation idealizes the creation and optimization of a space for a project which will promote environmental sustainability and the heritage of the institution in order to promote the enrichment of culture and promote the performing arts, with this we can say that creative and innovative projects fascinate the world of learning and entertainment theater will shape the arts experience on campus as it continually seeks new ways to engage students beyond the traditional barriers of learning and entertainment. This creation arises from the need to improve the rudimentary skills of the study, learning and entertainment part, this open-air theater or theater with buses is presented as an artistic expression that takes place in the open sky where presentations can be performed of free expression, either by students or in conjunction with teachers or other private entities.
Keywords: project; culture enrichment; involve; rudimentary skills; free expression presentations